Analisis Kritis atas Pengakuan Pendapatan Biaya Penyambungan Listrik (Studi Kasus : Perusahaan Listrik Indonesia) - Prihartini, Ayuningtyas; Aria Farah Mita (Politeknik Ganesha Medan, 2024)
This study aims to look critically at the basis of changes in revenue recognition that occur in electricity connection costs in Indonesian electricity company. This case study focuses on examining the basis for the revenue recognition of electricity connection fees, where the substance of the transaction has not changed, but in terms of the accounting treatment it has undergone several changes. The research object was conducted on the Indonesian electricity company which is a single unit analysis and uses data collection techniques in the form of documentation and interviews. Data collection techniques in the form of documentation are carried out by studying public documents such as Financial Reports and Annual Reports. Meanwhile, the interview used semi-structured with open ends questions. Agency Theory is used as a basis for knowing the logic that influences decisions in preparing accounting policies. The result of the study shows that basically electricity connection is a continuous access so that revenue recognition is carried out over the time. In the prior assessment before implementation of PSAK 72, there was additional criteria which concluded that if the connection was carried out by the company as a result of regulations (laws), then this revenue could not be recognized over the time.